Analysis of the Relationships Betweet Economic and Industrial Activutues with Carbon Emission Level in Indonesia in the 1991-2022 Period - Madhani, Zahara; Shofwan (Journal of Development Economic and Social Studies, 2025)
Indonesia as a developing country, continues to strive to increase economic growth in order to realize the welfare of society. However, this economic growth is not free from negative impacts, such as the exploitation of natural resources and increasing environmental degradation. One of the significant impacts of economic and industrial activities is climate change, which is a serious challenge in achieving sustainable development. This study aims to analyze the relationship between economic and industrial activities and the increase in carbon emissions in Indonesia during the period 1991-2022. The data used in this study comes from the World Bank, Our World In Data, and BPS, with the analysis method applied is time series regression using the VECM model. The results of this study indicate that economic growth has a significant negative effect, while investment, energy consumption and exports have a significant positive effect on CO2 emissions in Indonesia from 1991 to 2022.